Improvement in seed quantity and quality of spring safflower through foliar application of boron and zinc under end-season drought stress. (9th May 2019) - Soheili-Movahhed, Somayeh; Khomari, Saeid; Sheikhzadeh, Parisa; Alizadeh, Bahram
Abstract: Seed yield and quality are affected by water stress occurring at the reproductive stage of crops. Foliar application of micronutrients has been introduced as an agronomic approach to cope with such conditions. This study was undertaken to evaluate the effects of born (B) and zinc (Zn) on seed quantity and quality of spring safflower under late season water deficit. The experimental design was a split factorial in an randomized complete block (RCB) with three replications. The results showed that water deficit during flowering and seed-filling significantly decreased almost all traits compared to control only in 2014. Averaged over the 2 years, seedling length and vigor index were increased by Zn in all irrigation regimes. Germination rate and seed weight were increased by B and Zn in all irrigation treatments. It was concluded that foliar application of 350 ppm B and 1000 ppm Zn can considerably enhance seed yield and quality of safflower grown under terminal drought.